PENGARUH PROFITABILITY, FIRM SIZE, DAN FINANCIAL LEVERAGE TERHADAP TINDAKAN INCOME SMOOTHING PADA PERUSAHAAN BUMN GO PUBLIC DI BURSA EFEK INDONESIA (2018-2022) - Hasanah, Sumrotul; Susanti, Santi; Indriani, Susi (CV. Denasya Smart Publisher, 2024)
This research aims to empirically test the partial and simultaneous influence between the independent variables profitability, firm size and financial leverage with the dependent variable income smoothing in BUMN Go Public companies on the Indonesia Stock Exchange for the period 2018 to 2022. The population in this study is all BUMN Go Public companies listed on the Indonesia Stock Exchange totaling 20 companies with 5 years of observation. The research method used is a quantitative method with secondary data originating from the company's financial reports. The sampling technique used was simple random sampling with the final sample results being 80 total samples. The data analysis techniques used are descriptive statistical analysis, classic multicollinearity assumption test, overall model test, model feasibility test, classification matrix, logistic regression analysis, and hypothesis testing. The data was processed with the help of Eviews version 12 software. This research shows the following results: (1) Partially, the profitability variable has a significant positive effect on income smoothing. (2) Partially, the firm size variable has a significant negative effect on income smoothing. (3) Partially, the financial leverage variable has no effect on income smoothing. (3) Simultaneously all independent variables, profitability, firm size, and financial leverage are proven to have an effect on income smoothing.